2021
DOI: 10.1111/ijac.13986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonthermal plasma treatment on surface roughness and bond strength between veneer ceramic and zirconia core

Abstract: This in vitro study evaluated the effect of nonthermal plasma (NTP) treatment on the surface roughness (Ra) of the zirconia and the shear bond strength (SBS) between the veneer ceramic and the zirconia. Ninety zirconia specimens were divided into six groups according to the surface treatments applied: control with no treatment; sandblasting with 50‐μm Al2O3 particles; oxygen plasma treated for 5 min; oxygen plasma treated for 10 min; argon plasma treated for 5 min; and argon plasma treated for 10 min. Ra value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…5,6 NTP alters the surface energy of materials and increases the bond strength to surfaces subjected to plasma therapy. 7 Previous studies showed the positive effects of NTP on dentin-adhesive bond strength through exposing the functional groups of superficial dentin collagens, eliminating the smear layer, and enhancing the surface properties. 8,9 Dentinal tubules have shown improved hydrophilicity and increased penetration depth of adhesives following plasma therapy.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 NTP alters the surface energy of materials and increases the bond strength to surfaces subjected to plasma therapy. 7 Previous studies showed the positive effects of NTP on dentin-adhesive bond strength through exposing the functional groups of superficial dentin collagens, eliminating the smear layer, and enhancing the surface properties. 8,9 Dentinal tubules have shown improved hydrophilicity and increased penetration depth of adhesives following plasma therapy.…”
Section: Introductionmentioning
confidence: 99%